2022
DOI: 10.1002/jcsm.12928
|View full text |Cite
|
Sign up to set email alerts
|

Association between skeletal muscle mass and quality of life in adults with cancer: a systematic review and meta‐analysis

Abstract: Low skeletal muscle mass is known to be associated with poor morbidity and mortality outcomes in cancer, but evidence of its impact on health‐related quality of life (HRQOL) is less established. This systematic review and meta‐analysis was performed to investigate the relationship between skeletal muscle mass and HRQOL in adults with cancer. Five databases (Ovid MEDLINE, Embase via Ovid, CINAHL plus, Scopus, and PsycInfo) were systematically searched from 1 January 2007 until 2 September 2020. Studies reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 86 publications
1
29
0
1
Order By: Relevance
“…First, this was a prospective study that utilized a comprehensive set of indicators for patient evaluation. Most recent investigations examining sarcopenia in cancer have used a retrospective study design [ 4 , 5 ]. In these studies, the indicators of sarcopenia were single, failing to comprehensively evaluate sarcopenia and ultimately affecting the quality of the evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, this was a prospective study that utilized a comprehensive set of indicators for patient evaluation. Most recent investigations examining sarcopenia in cancer have used a retrospective study design [ 4 , 5 ]. In these studies, the indicators of sarcopenia were single, failing to comprehensively evaluate sarcopenia and ultimately affecting the quality of the evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia, which is characterized by a progressive and generalized loss of muscle mass and muscle function [ 1 ], affects more than 50 million people worldwide, and the number of affected individuals is expected to exceed 200 million in the next 40 years [ 2 ]. Sarcopenia has been shown to be associated with nutritional health and to result in severely reduced health-related quality of life (HRQOL) [ 1 , 3 , 4 ]. A growing body of research has revealed that preoperative sarcopenia is associated with worse survival in patients with cancer [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced physical function is often reported by hematological cancer patients and is associated with poor overall quality of life. A recent systematic review and meta-analysis showed that low muscle mass was associated with poorer physical functioning domain and global health-related quality of life (HRQOL) scores, as well as a longitudinal association between changes in skeletal muscle and several HRQOL domains in adults with cancer [ 8 ]. Loss of muscle mass and strength in those with hematological cancer seem to be attributed to the interplay among the cytotoxic effects of chemotherapy [ 9 , 10 ], the treatment’s side-effects and the disease itself [ 11 , 12 , 13 ], resulting in reduced oral intake and low energy.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle is essential to life and plays an essential role in movement, eating, and breathing. Conditions associated with muscle atrophy, therefore, have far-reaching implications for not only quality of life [1], but if severe can also impact mortality [2]. In this respect, cancer and its treatment can adversely affect skeletal muscle, causing atrophy, impaired contractility and mitochondrial dysfunction [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%